ANTIARRHYTHMIC ACTIVITY MONOGAMISTIC AMIDES AND HYDRAZIDES 1,4-DICARBOXYLIC ACIDS - N. V. Kolotova; I. P. Rudakova (Разработка и регистрация лекарственных средств, 2019)
The antiarrhythmic activity of 19 derivatives 1,4-dicarboxylic acids in experiments on white mice on the model of chlorocalcium arrhythmia and acute toxicity of 6 compounds. As a standard, the drug «Lidocaine» was used. Two compounds showed an antiarrhythmic effect exceeding the standard effect by 6 times [ED50=7.3 mg/kg (5.3÷10.0)] and 3 times [ED50=6.9 mg/kg (5.0÷9.5)]. 4-Aminobenzoylhydrazide itaconic acid has antiarrhythmic activity, the same derivatives of succinic, maleic, citraconic and dimethylmaleic acids are not active. Isonicotinoylhydrazide phthalic acid exceeds the antiarrhythmic activity of the standard, the same hydrazides of maleic, dimethylmaleic and tetrachlorophthalic acids do not possess an antiarrhythmic effect.